Removal of Chromium(VI) Ions from Aqueous Solutions and Industrial Effluents Using Magnetic FeO Nano-particles - K.M. Meera Sheriffa Begum; N. Anantharaman (Adsorption Science & Technology)
The adsorption characteristics of magnetic Fe 3 O 4 nano-particles synthesized by chemical co-precipitation for the removal of chromium(VI) ions from aqueous solutions and tannery effluents have been studied. The composition, size, morphology and magnetic properties of the nano-particles were characterized by FT-IR, XRD, TEM and VSM methods, respectively. Experiments were conducted in batch mode to observe the influence of different parameters such as pH, feed concentration, adsorbent dosage and temperature on the performance of the adsorbent. It was found that when the pH of the system was decreased from 7 to 2, the extent to which Cr(VI) ions were removed increased from 54% to 77%. The adsorption process was found to follow second-order kinetics and the rate constant was evaluated at 30 °C. The Langmuir isotherm was found to provide a good fit to the experimental data. The adsorption capacity of magnetite nano-particles towards Cr(VI) ions at room temperature was 2.9508 mg/g, with the value increasing to 3.4454, 3.7592 and 4.0475 mg/g at 40 °C, 50 °C and 60 °C, respectively. On the basis of the adsorption free energy change of 16.577 kJ/mol obtained at 30 °C, the adsorption mechanism was confirmed as being chemical in nature. The thermodynamic parameters for the adsorption process were also calculated from the experimental data. At an S/L ratio of 0.2 and under optimized conditions of pH, temperature and agitation, the removal of Cr(VI) ions from aqueous solution amounted to 85%. Regression analysis was performed and a correlation between percentage removal and operating parameters obtained.